Pengembangan Jiwa Wirausaha dan Kreativitas Siswa SD: Upaya Peningkatan Kualitas Pendidikan Melalui Pendekatan Edupreneur - Nurul Badriyah; Setyo Tri Wahyudi; Radeetha; Kartika Sari; Rihana Sofie Nabella (Universitas Serang Raya, 2024)
Education is considered a crucial factor in measuring a nation's progress and the morality of individuals and the state. Entrepreneurship education at the elementary school (SD) level is critical to shaping students' entrepreneurial character from an early age. The community engagement activities at Madrasah Diniyah Darul Ulum have successfully provided a fundamental understanding of entrepreneurship through a theory and practice approach involving active student participation. This approach creates an interactive and empowering learning environment. Students who were initially hesitant to speak became more confident and creative in expressing their ideas. These activities reinforce the foundation of entrepreneurial understanding and equip students with the practical skills needed to initiate and run small businesses. To enhance the effectiveness of entrepreneurship education, it is recommended to continue these activities by organising entrepreneurship fairs or business bazaars, providing a real platform for students to apply their knowledge and skills in the entrepreneurial world.